Experimental and numerical analysis of a helical coil solar cavity receiver: Thermal oil as the heat transfer fluid - Kumar A.; Shukla S.K. (My University, 2025)
The paper presents the novel design of double glazing helical coil solar cavity receiver for solar thermal applications. Performance model has been developed for the experimental setup based on energy balance equations. The results obtained were compared with horizontal tube receiver for the same experimental setup. The result shows that the 87.96% improvement in the convective heat transfer coefficient for the double glazing helical coil solar cavity receiver. Maximum conversion efficiency achieved is 21% more than that would be obtained for horizontal tube receiver. This paper also investigates how the quality of vacuum degraded with the temperature of the glass cover. © 2019, © 2019 Taylor & Francis Group, LLC.